Catastrophic Antiphospholipid Syndrome: A Case Series - Christopher, Navya; Periaswamy, Gopinath; Arunachalam, Venkatesh Kasi; Mangalakumar, V.; Mehta, Pankaj; Cherian, Mathew (Indian Journal of Radiology and Imaging, 2022)
Catastrophic antiphospholipid syndrome (CAPS) is the rare but most severe form of antiphospholipid syndrome with multiple organ ischemia developing over a short period of time. CAPS should be considered when imaging suggests an acute and concurrent multiorgan ischemia, associated with positive antiphospholipid antibodies. As CAPS can have fulminant irreversible complications, its early recognition is important to initiate the treatment promptly. We present three patients of CAPS who were managed at our institution.
Keywords: antiphospholipid syndrome; CAPS; catastrophic antiphospholipid syndrome